Tensile behavior of tetragonal zirconia micro/nano-fibers and beams in situ tested by push-to-pull devices - Zeng, Xiao Mei (2022)
The tensile mechanical behavior of tetragonal zirconia micro/nano-fibers and beams was studied with push-to-pull (PTP) devices equipped in an in situ nanoindenter. The small-volume ceramics generally experienced linear elastic deformation before fracture. Polycrystalline and oligocrystalline micro/nano-fibers exhibit a tensile strength of ∼0.9–1.4 GPa, while single-crystal beams exhibit a much higher tensile strength (∼2.1–3.2 GPa). The tensile strength of the small-volume zirconia is found comparable to the corresponding compressive strength, which indicates the large discrepancy between the tensile and compressive strength observed in bulk zirconia becomes insignificant at micro/nano-scales. No martensitic transformation induced shape memory strain was detected in the zirconia fibers and beams. Further variation in dopant concentration and crystal orientation was explored for single-crystal beams and their significance in controlling the tensile strength was discussed. Our work offers a new insight into the mechanical behavior of tetragonal zirconia-based ceramics at small scales.